Growth and physiological changes in continuously cropped eggplant (Solanum melongena L.) upon relay intercropping with garlic (Allium sativum L.) - Wang, Mengyi; Wu, Cuinan; Cheng, Zhihui; Meng, Huanwen (Frontiers in Plant Science, 2015)
Relay intercropping represents an alternative for sustainable production of vegetables, but the changes of internally antioxidant defense combined with the growth and yield are not clear. Field experiment was carried out to investigate the malondialdehyde (MDA) content and activity levels of superoxide dismutase (SOD), peroxidase (POD), polyphenol oxidase (PPO) and phenylalanine ammonia-lyase (PAL) in eggplant (Solanum melongena L.) and plant height, stem diameter, maximal leaf area and yield of eggplant grown under successive cropping in the year 2011 and 2012 to see if relay intercropping with garlic (Allium sativum L.) could benefit to eggplant growth and yield. Three experimental treatments with three repeats in each were carried out (completely randomized block design): eggplant monoculture (CK), eggplant/normal garlic relay intercropping (NG), and eggplant/green garlic relay intercropping (GG). In both years, the MDA content was significantly lower and SOD and POD activities were generally lower in NG and GG compared with CK in most sampling dates. PPO activity trends were generally opposite to those of POD. The general trend of PAL activity was similar to MDA. The plant height and stem of eggplant was lower, but the maximal leaf area was larger in NG and GG in 2011; in 2012 the plant growth was stronger in relay intercropping treatments. For eggplant yield in 2011, NG was 2.85% higher than CK; after the time for the green garlic pulled out was moved forward in 2012, the yield was increased by 6.26% and 7.80% respectively in NG and GG. The lower MDA content and enzyme activities in relay intercropping treatments showed that the eggplant suffered less damage from environment and continuous cropping obstacles, which promoted healthier plant. Thus from both the growth and physiological perspective, it was concluded that eggplant/garlic relay intercropping is a beneficial cultivation practice maintaining stronger plant growth and higher yield.